2018
DOI: 10.1051/matecconf/201817809016
|View full text |Cite
|
Sign up to set email alerts
|

Modern technologies of wastewater treatment for low-capacity facilities

Abstract: The article touches upon the issues of wastewater treatment on the facilities of small capacity. The brief analysis of the current state is given. The paper reveals main problems to be solved that consider small treatment plant operation, its influence on environment and most prospective solutions. The article considers the developed wastewater treatment technologies, as well as the implementation of these technologies on the patented small plants for deep biological treatment, including with the removal of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Presumably it is connected to peculiarities of feed structure and easy access to oxygen. The anoxic areas biofilm was unevenly distributed and has a "zone" of biomass growth During the study of biofilms was found that numbers of ciliates and rotifers are less than in the aerobic zone [6,7]. The investigated technological scheme can be used in the reconstruction of WWTP, especially in cases where the existing treatment plant scheme includes construction biofiltration where possible to achieve the required cleaning performance not only for BOD and nitrogen compounds [4].…”
Section: Studies Of the Pilot Model With Different Feed Materialsmentioning
confidence: 99%
“…Presumably it is connected to peculiarities of feed structure and easy access to oxygen. The anoxic areas biofilm was unevenly distributed and has a "zone" of biomass growth During the study of biofilms was found that numbers of ciliates and rotifers are less than in the aerobic zone [6,7]. The investigated technological scheme can be used in the reconstruction of WWTP, especially in cases where the existing treatment plant scheme includes construction biofiltration where possible to achieve the required cleaning performance not only for BOD and nitrogen compounds [4].…”
Section: Studies Of the Pilot Model With Different Feed Materialsmentioning
confidence: 99%